Selecting short-statured children needing growth hormone testing: Derivation and validation of a clinical decision rule - Bréart Gérard; Souberbielle Jean; Chemaitilly Wassim; Trivin Christine; Duché Laëtitia; Brauner Raja; Chalumeau Martin (BMC, 2008)
Abstract Background Numerous short-statured children are evaluated for growth hormone (GH) deficiency (GHD). In most patients, GH provocative tests are normal and are thus in retrospect unnecessary. Methods A retrospective cohort study was conducted to identify predictors of growth hormone (GH) deficiency (GHD) in children seen for short stature, and to construct a very sensitive and fairly specific predictive tool to avoid unnecessary GH provocative tests. GHD was defined by the presence of 2 GH concentration peaks < 10 ng/ml. Certain GHD was defined as GHD and viewing pituitary stalk interruption syndrome on magnetic resonance imaging. Independent predictors were identified with uni- and multi-variate analyses and then combined in a decision rule that was validated in another population. Results The initial study included 167 patients, 36 (22%) of whom had GHD, including 5 (3%) with certain GHD. Independent predictors of GHD were: growth rate < -1 DS (adjusted odds ratio: 3.2; 95% confidence interval [1.3-7.9]), IGF-I concentration < -2 DS (2.8 [1.1-7.3]) and BMI z-score ≥ 0 (2.8 [1.2-6.5]). A clinical decision rule suggesting that patients be tested only if they had a growth rate < -1 DS and a IGF-I concentration < -2 DS achieved 100% sensitivity [48-100] for certain GHD and 63% [47-79] for GHD, and a specificity of 68% [60-76]. Applying this rule to the validation population (n = 40, including 13 patients with certain GHD), the sensitivity for certain GHD was 92% [76-100] and the specificity 70% [53-88]. Conclusion We have derived and performed an internal validation of a highly sensitive decision rule that could safely help to avoid more than 2/3 of the unnecessary GH tests. External validation of this rule is needed before any application.